2020
DOI: 10.1038/s41598-019-56642-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between 5-day decitabine and 7-day azacitidine for lower-risk myelodysplastic syndromes with poor prognostic features: a retrospective multicentre cohort study

Abstract: Numerous studies have analysed the clinical efficacies of hypomethylating agents (HMAs) in patients with myelodysplastic syndromes (MDS). However, reports that compare the two HMAs, decitabine and azacitidine, in patients with lower-risk (low and intermediate-1) MDS are limited. We compared 5-day decitabine and 7-day azacitidine regimens in terms of treatment responses, survival outcomes, and adverse events in patients with lower-risk MDS with poor prognostic features. The overall response rates (ORRs) were 67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
(63 reference statements)
1
7
0
Order By: Relevance
“…Our results are consistent with another study [ 30 ], which found a significant ORR improvement in the DAC regimen over the AZA regimen, and analyzed the prognostic response factors. The ANC was the only identified prognostic factor associated with the ORR to HMA.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with another study [ 30 ], which found a significant ORR improvement in the DAC regimen over the AZA regimen, and analyzed the prognostic response factors. The ANC was the only identified prognostic factor associated with the ORR to HMA.…”
Section: Discussionsupporting
confidence: 92%
“…There have been many other studies exploring the efficacies of AZA in LrMDS, and Table 5 summarizes the results of these studies 8–13,15–19,21,38,39 . For a 5‐day regimen, the reported HI and TI rates ranged from 38% to 50% and 33% to 60%, most of which were derived from prospective phase 2 trial 13,15–19 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been many other studies exploring the efficacies of AZA in LrMDS, and Table 5 summarizes the results of these studies. [8][9][10][11][12][13][15][16][17][18][19]21,38,39 For a 5-day regimen, the reported HI and TI rates ranged from 38% to 50% and 33% to 60%, most of which were derived from prospective phase 2 trial. 13,[15][16][17][18][19] Real-world data from the US prospective registry, where approximately 75% of patients received 5-day regimen, showed higher rates of HI (70.8%) and TI (74.5%) in a subset of LrMDS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study demonstrated that the progression-free survival (PFS) of patients with MDS was significantly better in groups receiving decitabine than 5-azacytidine. Similarly, decitabine induced 67.2% overall response rates (ORRs), while 5-azacytidine showed 44% [ 169 ]. Another small molecule is enoxacin, which has antibacterial activities and could boost the expression of miRNAs by interacting with TARBP2, a miRNA biosynthesis protein [ 170 ].…”
Section: Targeting Ncrnas As a Therapeutic Approach In Cancer Treatmentmentioning
confidence: 99%